DIGIDES-BASED SMART VILLAGE: A STUDY OF DIGITAL TRANSFORMATION IN BURAU VILLAGE GOVERNANCE - Chafifah Nurun An-Nisa M; Maghfira, Suci; Syaiful Syahrir; Wanda Astian; Hasrianti; Mutiara; Nurhikmah; Alika Ramadhani; Amelia Saputri Ranta; Ahmad Aswar; Abid Al-dizzy; Muh. Ruslan Abdullah; Hisbullah Nurdin (International Journal of Multidisciplinary Reseach, 2025)
The implementation of a Smart Village concept based on local wisdom represents a strategic approach to fostering inclusive and sustainable digital transformation in village governance. This article aims to describe a community service program implementing a Smart Village through the use of Digital Village applications (Digides) in Burau Village, Burau Subdistrict, East Luwu Regency. The program adopted an Asset-Based Community Development (ABCD) approach, emphasizing the optimization of existing local assets and community potential as the foundation for change. The methodology was carried out through several stages, including inculturation, asset mapping, participatory planning, program implementation, and reflection and evaluation. The results indicate that the adoption of Digides significantly improved administrative efficiency, transparency, and accountability, while also accelerating public service delivery. Furthermore, the development of visual communication media such as educational banners, informational signboards, and village infographics enhanced public information disclosure and community participation. The program also stimulated social transformation, reflected in increased digital literacy, active youth involvement as digital facilitators, and strengthened cross-social group collaboration. Overall, the integration of digital technology with local wisdom effectively reinforced community self-reliance and positioned Burau Village as a contextual, inclusive, and competitive model of Smart Village development.